Association Of Myopia And Axial Length With Risk Of Lattice Degeneration - Nuraniar Bariq Kinayoh; RIZA TRANSMISIA SARI; Nur Khoma Fatmawati (Universitas Airlangga, 2022)
Lattice degeneration is an abnormal condition of the peripheral retina caused by stretching and thinning of the peripheral retina layer. This condition could increassed risk of retinal detachment that can cause blindness. Lattice degeneration is often found on myopic eyes with increases axial length. This study is aimed to evaluate the relationship and risk ratio between lattice degeneration with axial length and myopia among Samarinda college students. This was a cross-sectional study through purposive sampling. All subject underwent ophthalmologic examination including refractive correction, IOLmaster and indirect ophthalmoscopy by an ophthalmologist. A total of 66 myopic eyes were studied. Lattice degeneration was significantly associated with axial length (P=0.002) and myopia degree (P=0.001). Lattice degeneration was more common in high myopia (69,2%) and in axial length >26 mm (68,76%). Increasing lattice degeneration was associated with high myopia (OR:2,754, P=0.026) and axial length (OR:2.290, P=0.278). Conclusion: high myopia and axial length can increase the risk of lattice degeneration.